2020
DOI: 10.1590/fst.01919
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and risk assessment due to presence of metals and pesticides residues in honey samples from the major honey producing forest belts and different brands

Abstract: Honey is consumed worldwide because of its nutritional, therapeutic and medicinal purposes. Generally it is perceived that honey reaches its consumer in pure form however this is not always true as contaminants can end up in honey. Thus this study was designed to check the presence of contaminants in honey samples. For this purpose 52 samples were collected from forest belts while 25 samples of national and international brands were purchased. Heavy metals zinc, iron, cobalt and copper were detected in all 52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Moreover, the increase in studies on the quality of honey has been showing the incidence of trace elements (Altunatmaz et al, 2018). These trace elements and pesticides had been monitoring, to seek an alternative and methods to improve the quality of Physicochemical, bioactive properties and antioxidant of Apis mellifera L. honey from western Paraná, Southern Brazil the honey produced (Yaqub et al, 2020). Demonstrating, even more, the importance of the georeferencing of production (Camargo et al, 2014) and denomination of origin of honey.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the increase in studies on the quality of honey has been showing the incidence of trace elements (Altunatmaz et al, 2018). These trace elements and pesticides had been monitoring, to seek an alternative and methods to improve the quality of Physicochemical, bioactive properties and antioxidant of Apis mellifera L. honey from western Paraná, Southern Brazil the honey produced (Yaqub et al, 2020). Demonstrating, even more, the importance of the georeferencing of production (Camargo et al, 2014) and denomination of origin of honey.…”
Section: Introductionmentioning
confidence: 99%
“…Trace or heavy metals can be absorbed by plants from the soil or water, taken up through the use of pesticides near the apiary (Aghamirlou et al, 2015). The presence of toxic metals in honey have been reported for honeys from Ethiopia (Adugna et al, 2020), Romania (Oroian et al, 2016;Bartha et al, 2020), Turkey (Erbilir & Erdogrul 2005), China (He et al, 2013), Iran (Aghamirlou et al, 2015;Sobhanardakani & Kianpour, 2016), Pakistan (El-Nahhal, 2020Yaqub et al, 2020) and results showed concentrations above the recommended limits. These recurrent observations call for urgent assessment of honey mineral quality in many developing countries including Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of insecticide residues in bee products is necessary for ensuring safety to consumers and bee populations (Fernández et al, 2002). Honeybees and their products can be effectively used as bioindicators of environmental pollution from miticides (Fell and Cobb, 2009), trace and heavy metals and metalloids (Zhelyazkova, 2012;Yaqub et al, 2020;Lazarus et al, 2021), polychlorinated biphenyls (Santos et al, 2021), DDT (Cervera-Chiner et al, 2020;Freitas et al, 2021) and various pesticides (Alghamdi et al, 2020;Choi et al, 2020;Bramlitt, 2021;Rodríguez-Martínez et al, 2021). Honeybees fly several kilometers all around from their apiaries and have access to a large area picking pesticides through various pathways like collection of contaminated nectar, pollen and resins (Tosi et al, 2018), through contact with contaminated crops and plants, inhalation from contaminated air, ingestion with polluted water and through direct application of miticides and pesticides (Bogdanov, 2006;Colin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%